Comparative mutational evaluation of multiple lung cancers by multiplex oncogene mutation analysis. Issue 11 (6th October 2018) - Takahashi, Yuta; Shien, Kazuhiko; Tomida, Shuta; Oda, Shinsuke; Matsubara, Takehiro; Sato, Hiroki; Suzawa, Ken; Kurihara, Eisuke; Ogoshi, Yusuke; Namba, Kei; Yoshioka, Takahiro; Torigoe, Hidejiro; et al.
Abstract : In patients presenting with synchronous or metachronous multiple lung cancer (MLC), it is important to distinguish between multiple primary lung cancer (MP) and intrapulmonary metastasis (IM). The present study was aimed at investigating the mutational profiles of synchronous/metachronous MLC and to compare the classification of paired tumors by multiplex gene mutation analysis with the histopathological evaluation. We carried out targeted sequencing of 20 lung cancer‐related oncogenes using next‐generation sequencing (NGS) in 82 tumors from 37 MLC patients who underwent surgical resection at our department. The patients were diagnosed as MP or IM cases based on the Martini and Melamed criteria, histopathological and gene mutational evaluations. Matching mutations between paired tumors was observed in 20 (54%) patients, who were diagnosed as IM cases by mutational evaluation. Patients who could not be clearly diagnosed by histopathological evaluation were classified as equivocal cases. Among the histopathological IM cases (n = 7), six (86%) were confirmed as IM cases also by mutational evaluation, and most of the paired tumors of these cases (n = 5) harbored multiple matching mutations. Among the histopathological MP cases (n = 17), mutational evaluation yielded a discordant diagnosis in eight (47%) cases. Of these, the paired tumors of four cases harbored multiple matching mutations, suggesting that the mutational diagnosis might be more suitable in these patients. Our findings suggest that multiplex mutational analysis could be a useful complementary tool for distinguishing between MP and IM in addition to histopathological evaluation. Abstract : For patients with multiple lung cancer (MLC), it is important to distinguish between multiple primary lung cancer (MP) and intrapulmonary metastasis (IM). In this research, we carried out targeted sequencing of 20 lung cancer‐related genes using next‐generation sequencing (NGS) for MLC patients and compared the histopathological diagnosis and the mutational diagnosis. Our results suggest that multiplex mutational analysis of MLC could be a useful complementary tool for distinguishing between MP and IM.